A4 1 Auroras at the Equator - Trebino, Claudia; Rajpra, Dhaval Manishkumar; Hamed, Hamza (Physics Special Topics, 2024)
This paper discusses the required strength of a geomagnetic storm to induce a visible aurora at the equator, evaluating it via the difference between the magnetic reconnection rate on the dayside (using a value of ∼ 150 kV) and the nightside of the Earth. The nightside reconnection rate is quantified by the Sym-H index, a measure of the magnetic perturbation due to the ring current. We report that although feasible, such an event would be comparable to the Carrington Event (HSYM = −1750 nT) [5], if not more devastating, requiring a Sym-H value of at least −1720 nT.